Campuses of consent : sexual and social justice in higher education - Kulbaga, Theresa A.; Spencer, Leland G. (University of Massachusetts, 2019)
"This new book for scholars and university administrators offers a provocative critique of sexual justice language and policy in higher education around the concept of consent. Complicating the idea that consent is plain common sense, Campuses of Consent shows how normative and inaccurate concepts about gender, gender identity, and sexuality erase queer or trans students' experiences and perpetuate narrow, regressive gender norms and individualist frameworks for understanding violence. Theresa A. Kulbaga and Leland G. Spencer prove that consent in higher education cannot be meaningfully separated from larger issues of institutional and structural power and oppression. While sexual assault advocacy campaigns, such as It's On Us, federal legislation from Title IX to the Clery Act, and more recent affirmative-consent measures tend to construct consent in individualist terms, as something "given" or "received" by individuals, the authors imagine consent as something that can be constructed systemically and institutionally: in classrooms, campus communication, and shared campus spaces"--